KEPASTIAN HUKUM PELAKSANAAN KLAUSA KERUGIAN KONSEKUENSIAL DALAM PERKARA WANPRESTASI BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR 1106.K/Pdt/2016 - Dharma Yuda Putra; Elwi Danil; Muhammad Hasbi (Lafadz Jaya Publisher, 2023)
Consequential Losses are losses on benefits received by the applicant at a later date or losses on lost profits received at a later date by the applicant, Considerations of Judges in Giving Decisions Related to Legal Certainty regarding the implementation of the consequential loss clause as a result of default, there is already a Supreme Court Decision Number.1106K/ Pdt/2016, but there are still many people who do not know about the Supreme Court Decision. With this research, the authors hope to be able to add to the knowledge of writers and the public as well as provide reference material for judges as a consideration if a similar problem occurs. The process of resolving the problem of claims for consequential loss clauses as a result of default can be submitted to court and prosecuted for immaterial damages. The form of compensation received by the parties due to default can be in the form of giving compensation as a result of default on an agreement, can be given in various combinations, including the provision of compensation (in the form of losses, costs and interest). Furthermore, in the literature and jurisprudence there are also several models of compensation for default, as follows: first, compensation specified in the agreement, second, expected compensation, third, cost reimbursement, fourth, restitution, compensation in the form of restitution, fifth, quantum meruit, Sixth, implementation of the agreement, in the provision of compensation in the form of implementation of the agreement is an obligation to carry out the agreement even though it is too late, with or without compensation.